2010
DOI: 10.1270/jsbbs.60.314
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression profile of the cinnamyl alcohol dehydrogenase gene and its association with lignification in the sorghum (Sorghum bicolor (L.) Moench) bmr-6 mutant

Abstract: Lignin, one of the major components of plant cell walls, has negative impacts on forage digestibility and bioethanol production through fermentation. Understanding the regulatory mechanism of lignin biosynthesis is essential to developing plants with altered lignin contents. The sorghum (Sorghum bicolor [L.] Moench) brown-midrib-6 mutant (bmr-6) has reduced levels of several key enzymes in the lignin biosynthesis pathway. Among the genes encoding these enzymes, the gene for cinnamyl alcohol dehydrogenase (CAD;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…A number of the BMR mutants of sorghum have been identified and characterized since the late 1970s, two of which mutants, BMR-6 and BMR-12, appeared to be the most promising for improvement of forage quality (Porter et al, 1978;Tsuruta et al, 2010). Previous studies on ADL content of BMR-6 and -12 genes to each other were very limited except for Oliver's research (Oliver et al, 2005) which reported that the BMR-12 had significantly (P < 0.05) less ADL content than BMR-6 counterparts at dough stage, and the similar results were confirmed in our research that BMR-12 populations had significantly (P < 0.05) lower ADL content than that of BMR-6 at the later growing stage (milk and Dough) ( Fig.…”
Section: Differences In Adl Content Of Bmr-6 and Wmr-12 Forage Sorghumentioning
confidence: 99%
See 1 more Smart Citation
“…A number of the BMR mutants of sorghum have been identified and characterized since the late 1970s, two of which mutants, BMR-6 and BMR-12, appeared to be the most promising for improvement of forage quality (Porter et al, 1978;Tsuruta et al, 2010). Previous studies on ADL content of BMR-6 and -12 genes to each other were very limited except for Oliver's research (Oliver et al, 2005) which reported that the BMR-12 had significantly (P < 0.05) less ADL content than BMR-6 counterparts at dough stage, and the similar results were confirmed in our research that BMR-12 populations had significantly (P < 0.05) lower ADL content than that of BMR-6 at the later growing stage (milk and Dough) ( Fig.…”
Section: Differences In Adl Content Of Bmr-6 and Wmr-12 Forage Sorghumentioning
confidence: 99%
“…Previous research suggested two enzymes exhibit reduced activity as the result of BMR mutations, the activity of cinnamyl alcohol dehydrogenase (CAD) was decreased in bmr-6 sorghum (Tsuruta et al, 2010) while the activity of caffeic acid O-methyltransferase (COMT) was reduced in the bmr-12 mutants (Bout and Vermerris, 2003). Therefore, it can be deduced that there were not significant (P > 0.05) differences in relative expression level of CAD and COMT genes from joint to head stage ( Fig.…”
Section: Differences In Adl Content Of Bmr-6 and Wmr-12 Forage Sorghumentioning
confidence: 99%
“…The brown midrib mutants in sorghum were chemically induced via the mutagen diethyl sulfate (DES) (Porter et al 1978), a monofunctional alkylating agent that acts primarily as a base-substitution mutagen and has specificity for G/C-to-A/ T transitions (Hoffman 1980). In previous reports, base substitutions resulting in premature stop codons were identified in the coding regions of the genes encoding COMT (Bout & Vermerris 2003) and CAD (Saballos et al 2009, Sattler et al 2009, Tsuruta et al 2010) in sorghum brown midrib mutants (Table 5). In these mutants, the binding site of the enzyme has been changed, resulting in a loss of enzymatic activity.…”
Section: Sorghummentioning
confidence: 99%
“…Bout & Vermerris (2003) have developed cleaved amplified polymorphic sequence (CAPS) markers to identify the bmr-12 and bmr-18 genotypes, while we have developed single-nucleotide polymorphism (SNP) markers to identify the bmr-6 genotype. A comparison of the sequences derived from N-6 and bmr-6 revealed a C-to-T transition in the third exon of bmr-6, leading to a single amino acid alteration (glutamine to a termination codon; Tsuruta et al 2010). To verify the single base-pair change observed in bmr-6, SNP markers were developed to distinguish the wild-type and mutant CAD alleles (Fig.…”
Section: Sorghummentioning
confidence: 99%
See 1 more Smart Citation